2009
DOI: 10.1039/b815544p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of polyimide formation

Abstract: The reactions of 3,4,9,10-perylenetetracarboxylic dianhydride with 4,4'-diamino-p-terphenyl and with 2,4,6-tris(4-aminophenyl)-1,3,5-triazine on an Au(111) surface have been followed by low-temperature UHV-STM in the range of 300 to 700 K at coverages of up to one monolayer. Well-ordered, H-bonded structures are observed even after annealing at temperatures up to 470 K, while above 550 K reaction is initiated with evidence of amic acid intermediates. At higher temperatures, full imidisation leads to a covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…6A). [60,61] In solution and in thin films, the amic acid reaction intermediate is readily formed at room temperature, whereas on Au(111) structures ascribed to amic acid species (Fig 6B) can only be observed after annealing to above ~470 K. [61] As outlined in the previous section, below this temperature, the two species form highly ordered nanostructures stabilized by hydrogen bonds. [50] The restriction of the two reaction partners to two dimensions hence considerably raises the activation barrier for the first reaction step which is intuitively plausible since the nucleophilic backside attack involved in this step requires an offset between the reaction partners, which might only be reached at higher temperatures where vibrational amplitudes of either of the reactants orthogonal to the surface become significant.…”
Section: Surface Chemistry Approaches To Low-dimensional Polymeric Namentioning
confidence: 95%
See 2 more Smart Citations
“…6A). [60,61] In solution and in thin films, the amic acid reaction intermediate is readily formed at room temperature, whereas on Au(111) structures ascribed to amic acid species (Fig 6B) can only be observed after annealing to above ~470 K. [61] As outlined in the previous section, below this temperature, the two species form highly ordered nanostructures stabilized by hydrogen bonds. [50] The restriction of the two reaction partners to two dimensions hence considerably raises the activation barrier for the first reaction step which is intuitively plausible since the nucleophilic backside attack involved in this step requires an offset between the reaction partners, which might only be reached at higher temperatures where vibrational amplitudes of either of the reactants orthogonal to the surface become significant.…”
Section: Surface Chemistry Approaches To Low-dimensional Polymeric Namentioning
confidence: 95%
“…This smaller size might be due to kinetic limitations during growth and/or to steric hindrance. Interestingly, the confinement of the imidization condensation reaction to the surface appears to increase the proportion of iso-imide reaction products, [61] where the nitrogen has replaced the carbonyl oxygen instead of the bridging oxygen in the final product. This is tentatively ascribed to a lower strain energy of both the intermediate and final reaction products of the iso-imide in the constrained geometry on Au(111).…”
Section: Surface Chemistry Approaches To Low-dimensional Polymeric Namentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, one can envisage the construction of 2D nanoporous H-bonded networks, MOFs, or architectures constructed via controlled covalent assembly. Many examples exist of such architectures formed both under UHV conditions [81][82][83][84][85][86][87] and at the liquid-solid interface [88][89][90][91]. Pores designed to have a suitable (chiral) shape and dimension could act as hosts for prochiral reagents.…”
Section: Formation Of Supramolecular Assembliesmentioning
confidence: 99%
“…Recently it was demonstrated that polyimide strands can be formed from a hydrogen-bonded PTCDA-DATP superstructure on Au͑111͒ by annealing. 22,23 From these experiments it was concluded that the confinement to the surface raises the energy barrier to form the amic acid reaction intermediate, cf. scheme in Fig.…”
mentioning
confidence: 99%